Breastfeeding Rate, Food Supplementation, Dietary Diversity Among Children Aged 6–59 Months, and Associated Factors in Papua New Guinea - Pham, Bang Nguyen; Silas, Vinson D.; Okely, Anthony D.; Pomat, William (Frontiers in Nutrition, 2021)
Objective: To examine breastfeeding rate, food supplementary, dietary intake and diversity among children aged 6-59 months, and to identify associations with household and maternal socioeconomic demographic factors in PNG. Method: Data from 2943 children were extracted from the Comprehensive Health and Epidemiological Surveillance System database, operated by PNG Institute of Medical Research and used to estimate breastfeeding rate, food supplementation, and dietary intake of CU5 in a typical week. Dietary diversity score (DDS) was used as a proxy indicator to measure nutrient adequacy. Associations of DDS with household and maternal socioeconomic and demographic factors were examined using multivariate logistic regression analysis. Result: Breastfeeding rate among children aged 6-8 months was 85% (70% in urban and 90% in rural sectors) and 50% of children of this age group were fed with supplementary foods. 20% of children aged 6-23 months were currently breastfed and received solid, semi-solid and soft foods 3 times or more per day. 48% of children aged 6-59 months had total DDS below the average level (23 scores). Place of residence, mother education and household wealth were associated with dietary diversity among studied children. Children in urban areas are 10% more likely to have lower level of total DDS than those children in rural areas (OR: 1.11 [0.79-1.56; p-value: 0.5). Children whose mothers with primary education level were 1.6 folds more likely to have lower level of total DDS than children whose mothers had vocational training or college education (OR: 1.63 [0.68-3.92]; p-value: 0.28). Children from poorest households were 1.2 folds more likely to have lower DDS than those from richest households (OR: 1.22 [0.79-1.87]; p-value: 0.37). Discussion: A range of factors has been identified, contributing to the eating behaviors among CU5 in PNG, in which mother education and household wealth are among the most important determinants of childhood dietary diversity as they have direct affect on accessibility to and affordability for a variety of foods at the household level. Conclusion: Evidence-based integrated and comprehensive approaches are needed to improve women education and household wealth, contributing to the improvement of food diversity among young children in PNG.